Manajemen Pembelajaran Kurikulum Merdeka di Taman Kanak-kanak Khalifah Carocok Anau Kabupaten Pesisir Selatan - Yuslia Yeni, Herfina; Zulminiati, Zulminiati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this research is to find out how the independent curriculum learning management is managed in the Khalifah Carocok Anau Kindergarten in the South Coastal Region. This researcher is a participant in a qualitative study that describes the planning, implementation, and assessment of the independent curriculum in kindergarten. Information is collected from various sources, including observation, interviews, and documentation. To process all the collected data used data analysis, especially descriptive analysis. Based on research findings, the management of independent curriculum learning includes planning, implementation, and assessment processes. Learning planning consists of annual programs, semester programs, and teaching modules. Where co-curricular, extra-curricular and intra-curricular activities are used to complete the learning process. Every Monday to Thursday, students take part in intracurricular learning, and every Saturday students take part in extracurricular learning. For Friday imtaq-based lessons. In one semester, two learning projects are completed. Different content, products and results are used to carry out learning in a differentiated way. The implementation of independent curriculum learning is carried out by giving independence to children to carry out activities. Assessment of learning emphasizes the process not the result. The assessment process is carried out in the form of early learning activities, during the learning process and at the end of learning activities